Problematika Komunikasi Orang Tua dan Sikap Sosial Anak Zaman Now di Komplek Perumahan Ogan Permata Indah Palembang - Saipul Annur (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2019)
The relationship between parents and children will influence the communication of children with parents, if children and parents are less familiar, it will automatically have an impact with passive communication, so it will make parents difficult to control the development of the child. The study aims to determine the social attitudes of children, parental communication with children, and factors that influence the problem of parental communication on the social attitudes of children in the Jakabaring OPI Palembang Complex. Research Subjects were Parents and Children in the Jakabaring OPI Complex. The research method is qualitative with the design of research phenomena with methods of structured observation, interviews and documentation. Data analysis Using descriptive includes reduction, display and verification. The results of the study are as follows: The attitudes and social behavior of children in the housing complex environment are still well controlled, only when observed from the side of the relationship with parents and their families tend to be passive and rather arrogant. Children sometimes argue and differ opinions that give rise to the attitude of avoiding the anger of parents, so some of them choose to go out of the house. The pattern of parental communication with children is not consistent with what the parents themselves want. Especially their treatment of children who tend to be authoritarian and too dictating, so children feel depressed and feel completely wrong in doing. Factors that affect the problem of parents communication with children; Psychological atmosphere of communication, parent leadership, language used in communicating with children by parents, children's living environment, and school environment where children spend almost seven hours one day at school.